Successful Decriminalization of Narcotics Abusers in Thailand: Kesuksesan Dekriminalisasi Penyalahguna Narkotika di Thailand - Arie Ramadhani; Desi Yunita Putri; Ratna Wulandari; Atim Hariyadi (SOSIOEDUKASI, 2024)
The aim of this research is to compare the concept of decriminalization of narcotics abusers in Thailand and Indonesia, and determine the best concept that can be implemented in Indonesia because decriminalization in Indonesia has not been effective.The type of research used is pure normative legal research, with a comparative approach. The results of Thailand's research in changing policies for decriminalization followed by changes to law enforcement and the criminal justice system, this is very different from our country. The lack of clarity in the legal substance, in this case the Narcotics Law, is the main reason for the failure to implement decriminalization for narcotics abusers. No less important is the culture of law enforcement and society in viewing the decriminalization of narcotics abusers in Indonesia which hinders rehabilitation efforts for narcotics abusers. Different from Thailand, because overcoming narcotics abusers is Thailand's national development agenda, the War of Drugs is carried out with drug control and support from the local community, thereby changing the culture of viewing narcotics abusers as patients, not criminals, which is also accompanied by the construction of rehabilitation facilities and infrastructure in each region. where this has not been done by the government of our country.